Breeding agricultural plants - Leidigh, Arthur H. (My University, 1902)
Introduction: It pays to have the best; disregarding mere appearances and looking at it altogether from the commercial side—it pays. Our cattle, our vegetable garden and our flowering plants are all the product of breeding with its consequent care and attention. It has been but a few years since our cattle were all of the long narrow type; poor feeders, slow of growth, small at the finish, making inferior meat and not markedly prolific. Now we find well bred cattle here; they out-weigh and out-sell the range cattle, are better feeders, early maturing and prolific. Care and selection, adaptation to a specific use and familiarity with the climate have brought about these things, giving us an increase in quality and in quantity at the same time. It is thus with few exceptions in the case of all animals. Among plants we find the pansy, the aster, the violet and many more of our well known flowering plants have been more than doubled in size and quadrupled in beauty within recent years and this too accompanied by a greater range of growth. The plants of the vegetable garden suffer many changes, some running out, others being displaced, but always changing because we set an ideal by our desires, and a more prolific article or a product of find quality is always sought. Since the gardener at the most must be governed largely by the amount of profit the given variety will yield him he uses the desirable and soon the neglected varieties are out of date, the seed man ceases to grow them and they disappear.
Citation: Leidigh, Arthur H. Breeding agricultural plants. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Horticulture; Agriculture; Plant Breeding; Seeds; Theses